ANALISIS PENERAPAN STANDAR AKUNTANSI KEUANGAN NO. 101 TENTANG LAPORAN KEUANGAN SYARI’AH (Studi Kasus KSPPS BTM BINA MASYARAKAT UTAMA (BiMU)) - Mamun, Sukron; Sismona, Erlinda (DPPM Universitas Pelita Bangsa, 2020)
This research was conducted at KSPPS BTM BiMU. The purpose of this research is to find out whether the financial reporting of KSPPS BTM BiMU is in accordance with the applicable Financial Accounting Standards. This research method uses a qualitative approach with descriptive methods, namely methods that characterize the actual situation. Which means there is no intervention from of the researcher in the form of reducing or adding the data. While the data retrieval technique is by observation, direct interview with KSPPS BTM BiMU manager related to the financial report, and documentation in the form of the 2017 KSPPS BTM BiMU annual report.From the results of this research which was conducted on KSPPS BTM BiMU there are several problems that were found, among others: in the financial statements presented, temporary syirkah funds is still combined with liability posts on the balance sheet KSPPS BTM BiMU. KSPPS BTM BiMU was found does not make several reports such as reports on changes in tied investment funds, income reconciliation reports and profit sharing, reports on sources and uses of zakat funds and reports on sources and uses of benevolent funds.The results showed that the financial statements of KSPPS BTM BiMU had not been fully compliant with PSAK 101 because it was incorrecty structured and several reports were incomplete. This study can be a reference material for education and Sharia Cooperative practitioners